2011
DOI: 10.1002/bsl.1993
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neuroimaging Evidence on Mock Juror Decision Making

Abstract: During the penalty phase of capital trials, defendants may introduce mitigating evidence that argues for a punishment "less than death." In the past few years, a novel form of mitigating evidence-brain scans made possible by technological advances in neuroscience-has been proffered by defendants to support claims that brain abnormalities reduce their culpability. This exploratory study assessed the impact of neuroscience evidence on mock jurors' sentencing recommendations and impressions of a capital defendant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 32 publications
4
71
3
Order By: Relevance
“…In addition, especially in death penalty cases, it appears increasingly common for genetic and neuroimaging data to be used in tandem (Bernet et al, 2007), which we explored in these cases as well. The previous literature shows varying and inconsistent effects of neuroimaging evidence in criminal cases (Greene & Cahill, 2012; Schweitzer et al, 2011; Saks et al, 2014), resembling our findings here. Neuroimaging evidence did not affect the outcome in the non-capital sentencing case and had an inconsistent effect in the death penalty case, where it reduced the likelihood of a death penalty compared with an impulsivity claim, but not when neuroimaging evidence was paired with genetic evidence.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, especially in death penalty cases, it appears increasingly common for genetic and neuroimaging data to be used in tandem (Bernet et al, 2007), which we explored in these cases as well. The previous literature shows varying and inconsistent effects of neuroimaging evidence in criminal cases (Greene & Cahill, 2012; Schweitzer et al, 2011; Saks et al, 2014), resembling our findings here. Neuroimaging evidence did not affect the outcome in the non-capital sentencing case and had an inconsistent effect in the death penalty case, where it reduced the likelihood of a death penalty compared with an impulsivity claim, but not when neuroimaging evidence was paired with genetic evidence.…”
Section: Discussionsupporting
confidence: 89%
“…Importantly, our estimation approach avoids the dichotomous thinking that dominates media discourse of popular psychological effects and, instead, emphasizes-in accord with APA standards-interpretation of results based on point and interval estimates. Furthermore, research in the domain of jury decision making suggests that brain images have little or no independent influence on juror verdicts-a context in which the persuasive influence of a brain image would have serious consequences (Greene & Cahill, 2012;. Taken together, these findings and ours present compelling evidence that when it comes to brains, the "amazingly persistent meme of the overly influential image" 3 has been wildly overstated.…”
Section: Resultsmentioning
confidence: 50%
“…and found that, although jurors found neuroscience-based testimony more convincing than non-neuroscience-based testimony, brain images had no additional effects on juror decision-making over and above the text-based expert testimony they accompanied. Similarly, Greene and Cahill (2012) found that brain images had no greater impact than neuropsychological evidence on sentencing recommendations. Taken together, the evidence seems to suggest that expert neuroscience testimony can influence jurors, but brain images themselves play a small role, if any.…”
Section: Introductionmentioning
confidence: 99%